2014
DOI: 10.1007/s11239-013-1046-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rivaroxaban versus low-molecular-weight heparin therapy in patients with lower limb fractures

Abstract: Thromboprophylaxis with rivaroxaban has proved effective and safe in patients undergoing hip and knee replacement surgery. As it is unclear whether it is also effective and safe in fracture patients, the aim of the present study was to evaluate the efficacy and safety of rivaroxaban in patients with lower limb fractures. We performed a retrospective cohort study of 2,050 consecutive patients treated for lower limb fractures at our trauma center, comparing rates of venous thromboembolism (VTE), bleeding and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
0
24
2
1
Order By: Relevance
“…Factor Xa is the active form of the coagulation factor thrombokinase and is synthesised in liver. Long et al have recently shown that in comparison with LMW heparins rivaroxaban reduced the incidence of VTE by 45% without increasing the risk of bleeding in patients with lower extremity fractures [ 10 ]. Patients receiving rivaroxaban do not need to undergo daily injection or regular drug monitoring and therefore profit from a higher comfort and greater compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Factor Xa is the active form of the coagulation factor thrombokinase and is synthesised in liver. Long et al have recently shown that in comparison with LMW heparins rivaroxaban reduced the incidence of VTE by 45% without increasing the risk of bleeding in patients with lower extremity fractures [ 10 ]. Patients receiving rivaroxaban do not need to undergo daily injection or regular drug monitoring and therefore profit from a higher comfort and greater compliance.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients taking rivaroxaban were younger and with a lower number of fractures than patients taking LMWH. 19 All data on NOACs so far available in the field of emergency surgery are obtained in small cohorts or subgroups of patients and in retrospective studies; thus, we must be cautious of generalizing the results. Additional data from large and "ad hoc" studies in patients undergoing emergency hip fracture surgery are needed to provide evidence that NOACs are at least as effective and safe as LMWHs in emergency orthopaedic surgery.…”
Section: Risk Of Venous Thromboembolism and Available Evidence On Antmentioning
confidence: 99%
“…The evidence network for the primary analysis (figure 2) included 31 studies and six observational studies (52,(55)(56)(57)(58)62)) reporting on 287, 692 patients exposed to 230, 090 years of anticoagulant medication. We were unable to separate out upper and lower GI bleeds as most of the studies did not include this information.…”
Section: Major Gi Bleedingmentioning
confidence: 99%